Alternative waste management: composting and biochar conversion for metal remediation - Yuniwati, Eny Dyah; Novitasari, Dwi Rizki; Kamran, Ali (Assyfa Journal Scientific Essay, 2024)
Palm oil agribusiness drives agricultural economic growth the greatest. Developing palm oil agriculture can solve economic issues. Despite low productivity, swamp areas can be used to grow oil palm plants to increase palm oil production. Due to low plant cultivation technology use from sowing to harvest and soil amelioration, plant productivity needs to be maximized. This study will qualitatively synthesize all research data to investigate biochar and organic materials as soil fertility and productivity supplements in swamp terrain. This study summarises primary research using a systematic review. Peer-reviewed PDF-formatted scientific literature. Journal articles in Indonesian and English on Instagram's usefulness as a digital socialization medium, especially in government institutions, were chosen. The Harzing Publish or Perish software searched Google, ScienceDirect, and Emerald for relevant papers from the past five years. This literature review was synthesized using a narrative method to group similar retrieved data by outcomes measured to meet objectives. According to the results, palm oil biomass waste as compost or biochar is a realistic way to manage organic waste. Biochar can sink atmospheric carbon as a soil amendment by converting biomass into aromatic carbon, which degrades less. This article discusses how waste management increases biological decomposition.